A wave of lynching: Morality and authority in post-Tsunami ACEH - Enzo, Nussio and Clayton, Govinda (Comparative Politics)
Lynching is surprisingly prevalent today. Most research on it still focuses on the Southern U.S. after the Civil War. Other research on contemporary lynching provides detailed descriptions of lynching in particular contexts. However, there is a notable deficit in systematic analysis of theoretical arguments. In this Comparative Politics article, CSS$1 (BEnzo Nussio and Govinda Clayton extend prior work in developing a novel argument that explains contemporary lynching, which is being assessed using systematic evidence on lynching in Indonesia. The authors argue that two conditions can create a context ripe for lynching: shared morality around a salient collective threat and weak authority - Reproduceds
Keywords: Authority; Indonesia; Legitimacy; Lynching; Morality; Natural disaster; Violence